Free nutritious meals program or Makan Bergizi Gratis (MBG) and the rural political economy: A theory-driven literature review of urban bias, spatial justice, and fiscal dynamics in rural–urban relations - Ariyanto, Komang; Saharuddin, Saharuddin (Priviet Social Sciences Journal, 2026)
This article presents a theory-driven literature review of the Free Nutritious Meals Program or Makan Bergizi Gratis (MBG) through the lens of urban bias theory, structuring the analysis into four distinct pillars: economic opportunity, infrastructural constraints, political risk, and fiscal trade-offs. It examines whether the policy can reduce rural–urban disparities or reinforce the structural rural dependence on the central government. By systematically searching and synthesizing 22 core scientific publications from 2024 to April 2026 via the conceptual approaches of Snyder (2019) and van der Waldt (2021), guided by explicit inclusion and exclusion criteria, this review assesses the political‒economic implications of the MBG. The synthesis indicates that, based on policy projections and early modeling, MBG has the potential to serve as a rural economic stimulus through increased demand for local food, improvement in farmers’ terms of trade, and job creation within village-based food supply chains. Economic multiplier effects also emerge through household income redistribution and strengthening local agricultural product markets. However, the findings also reveal several structural constraints that may reinforce these biases. Documented logistical infrastructure limitations in 3T regions (disadvantaged, frontier, and outermost areas), such as the absence of cold chains and adequate food transportation access, create a reasonable inference that urban vendors will likely dominate food procurement in these areas. Furthermore, the centralized policy design increases the risk of local elite political patronage, the marginalization of microeconomic actors such as school cafeteria vendors, and potential budget leakage. From a fiscal perspective, the large allocation for the MBG creates pressure on financing sustainability and raises the risk of budget substitution away from productive rural sectors. This study concludes that MBG can become an effective instrument for reducing urban bias only if accompanied by governance decentralization, investment in rural logistics infrastructure, procurement transparency, and the integration of local economic actors. As a normative warning, without such reforms, the MBG risks becoming a consumptive policy that reinforces spatial inequality and rural dependence on the central government for funding.